CHARACTERISTICS AND TOXICITY OF NANOEMULSION FORMULATION OF PIPER RETROFRACTUM AND TAGETES ERECTA EXTRACT MIXTURES - Nuryanti, Ni Siluh Putu; Martono, Edhi; Ratna, Endang Sri; ., Dadang (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Characteristics and Toxicity of Nanoemulsion Formulations of Piper retrofractum and Tagetes erecta Extract Mixtures. Nanotechnology has been used in the developing of botanical insecticide formulation for improving its stability and effectiveness. The research was aimed to make nanoemulsion formulations of Piper retrofractum fruits and Tagetes erecta flowers extracts and to evaluate their toxicity against brown planthopper (Nilaparvata lugens [Stål]) nymphs. The development of nanoemulsion formulaions was carried out by using the low energy method with inversion phase emulsification.  The toxicity of the four formulations was tested against brown planthopper nymphs using a contact method. Four nanoemulsion formulations were obtained.  The study showed that in the developing of the formulations, the type and level of emulsifier materials affected the physical characteristics of formulas, such as stability, surface tension, viscosity, particle size, and particle morphology. The nanoemulsion formulation containing 1% of the mixture of P. retrofractum fruits and T. erecta flowers extracts, 1.75% Triton X-100 emulsifier showed the highest toxic on the brown planthopper nymph, with the LC95 value was 0.15%.  The study indicates that nanoemulsion formulation of P. retrofractum and T. erecta extracts are potential to be developed as botanical insecticide to control brown planthopper of rice.